Soil microarthropod populations under natural and planted fallows in southwestern Nigeria - Adejuyigbe, C.O.; Tian, G.; Adeoye, G.O. (1999)
Microarthropods, such as soil mites (Acari) and springtails (Collembola), with body width between 0.08 mm and 0.5 mm play important roles in soil fertility maintenance through their regulatory activities in decomposition and nutrient turnover. Observations were made at IITA, Ibadan, southwestern Nigeria to evaluate the effects of natural regrowth of vegetation – mainly the shrub Chromolaena odorata – and three planted woody fallow species (Acacia leptocarpa, Senna siamea, and Leucaena leucocephala) on soil microarthropods in a degraded Alfisol. Populations of soil microarthropods were higher in the rainy season than the dry season, and populations were greater under natural fallow than for continuous cropping with maize (Zea mays) and cassava (Manihot esculenta). Populations of soil microarthropods were comparable under leucaena and natural fallow, but populations in the rainy season were 38% higher under senna than natural fallow and 36% higher under acacia than natural fallow. Regression analysis indicated that soil microarthropod population under fallow species was positively correlated with the lignin contents of leaf litter.